Within or Beyond the University? Experiences of alternative higher education - Tristan McCowan; Gunther Dietz (Universidade Federal do Rio Grande do Sul, 2022)
Despite an important process of expansion and growth, higher education institutions around the world still reproduce exclusion, discrimination and inequality with regard to underrepresented and underprivileged communities and peoples, their knowledges and their languages. In this text, we briefly frame contemporary alternatives to mainstream higher education that - some within existing universities, some beyond conventional higher education structures - are working against the grain to address these failings. By introducing the case studies of alternative, intercultural, indigenous, decolonial, co-operative and/or social movement universities that make up this special issue, we identify institutional and organisational tendencies, topic issues and emerging theoretical contributions, thus aiming to develop a deeper understanding of the orientation and role of these institutions, their impacts and challenges faced.